Penguatan Literasi Siswa melalui Pendekatan Inovatif - Joko Purwanto; Umi Faizah; Eko Nurrahmad; Aiprillisa Mutia Dewi; Afra Azizah (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
Strengthening student literacy is one of the important aspects in improving the quality of education in Indonesia. Literacy is not only the ability to read and write, but also the ability to understand, analyze, and apply information. In this case, the role of teachers is also very much needed. The ability of teachers to manage and implement the learning process or the process of strengthening literacy is also very much needed. Therefore, it is necessary to have an understanding and mastery of various innovative approaches to improve students' literacy skills. This article aims to describe how teachers can apply various innovative approaches in order to improve student literacy at SMA N 6 Purworejo. The method of community service activities is carried out in the form of socialization, discussion and question and answer. The results of community service activities, various innovative approaches that can be applied by teachers, including, namely, innovating teacher involvement in reading activities before learning, involving technology in literacy learning, implementing project-based learning, and implementing collaborative approaches and thematic learning in the learning process.